2022
DOI: 10.1186/s11556-022-00307-y
|View full text |Cite
|
Sign up to set email alerts
|

The burden of mild cognitive impairment attributable to physical inactivity in Colombia

Abstract: Background Mild cognitive impairment often precedes dementia. The purpose of this analysis was to estimate the population attributable fraction for physical activity in Colombia, which is the reduction in cases that would occur if all participants were physically active. Methods The sample included 20,174 men and women aged 70.04 ± 7.68 years (mean ± SD) from the National Survey of Health, Wellbeing and Ageing. Trained interviewers administered a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Furthermore, significant regional differences show more older people in Jakarta engage in physical activity than in poorer regions such as Borobudur 32 . Research in Colombia has also shown that physical activity may substantially reduce the risk of MCI 53 . Public health strategies and interventions for enhancing overall health and reducing dementia risk in LMICs that focus on promoting physical activity may be best done via community centers in groups to ensure uptake and adherence 32 …”
Section: Modifiable Risk Factors For Dementiamentioning
confidence: 99%
“…Furthermore, significant regional differences show more older people in Jakarta engage in physical activity than in poorer regions such as Borobudur 32 . Research in Colombia has also shown that physical activity may substantially reduce the risk of MCI 53 . Public health strategies and interventions for enhancing overall health and reducing dementia risk in LMICs that focus on promoting physical activity may be best done via community centers in groups to ensure uptake and adherence 32 …”
Section: Modifiable Risk Factors For Dementiamentioning
confidence: 99%
“…It has been estimated that approximately 8% of dementia cases could be prevented if all adults were physically active [ 7 ]; for this reason, programs that aim to increase physical activity levels could be a potential strategy to substantially reduce the burden of mild cognitive impairment and consequent dementia [ 7 ]. It is expected that in Colombia, about 23% of patients with mild cognitive impairment would be prevented if older adults perform vigorous physical exercise [ 8 ]. Additionally, physical exercise can preserve the ability to perform activities of daily living and functional skills in older adults [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%